Marketing Mix Analysis Of Interest In Oyster Mushroom Cultivation - Fajar Handika; Andi Sitti Halimah; Nurhaeda Nurhaeda (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
Oyster mushroom is a saprophytic plant that lives on softwood and obtains food by utilizing the remains of organic matter. This study aims to analyze how much the new value of marketing has on oyster mushroom cultivation in Lapadde Village, Ujung District, Parepare City, and to find out what variables in the marketing mix influence interest in oyster mushroom cultivation in Lapadde Village, Ujung District, Parepare City. The method of determining the sample in this study used purposive sampling, purposive sampling, which is a technique based on certain considerations made by the researcher based on the characteristics or characteristics of the previously known population, then the researcher determined based on his considerations. The method of collecting data is by interviews, questionnaires, observation, and documentation. Instrument testing is carried out by testing the validation and reliability using the SPSS program. The data analysis method used is quantitative data analysis to identify the marketing mix in analyzing cultivation interest. So the results of this study indicate that the marketing mix which consists of price and promotion variables has a significant influence with a significance value below 0.05% while the product and place variables do not have a significant effect. While the marketing mix variable simultaneously influences cultivation interest.